Exploring Payment Pain in Food Purchases During Travel - METIN, Tugce; Bozgeyik, Yusuf; Arslan, İbrahim (International Journal of Contemporary Economics and Administrative Sciences, 2025)
This study examines the relationship between the pain of payment during food purchases by travellers and moderating variables such as income, trip planning duration, payment amount, and payment method. Two experimental studies were conducted, one in the United States and one in Turkiye. Results from Turkiye indicate that payment method and trip planning duration play a significant and positive moderating role in the relationship between the highest food purchase amount and the pain of payment. In the United States, however, the payment method was found to have a significant but negative moderating effect. Additionally, when income and trip planning duration were considered as independent variables, both the highest food purchase amount and total food expenditure during the trip had a significant and positive moderating effect on the pain of payment. This study discusses the "pain of payment" phenomenon, a cognitive bias in behavioral economics, in the context of tourism expenditures.